STAGES AND GEODYNAMIC SETTINGS OF EARLY PROTEROZOIC GRANITE FORMATION ON THE SOUTHWESTERN MARGIN OF THE SIBERIAN CRATON - Turkina O.M.; Bibikova E.V.; Nozhkin A.D. (My University, 2003)
Two discrete stages of the early proterozoic granitoid magmatism in the south-eastern margin of the Siberian craton are identified on the basis of the U-Pb-isotope studies on the granitoids from the Podporogskij massif. Formation of the granitoids of various geochemical types took place in the first of them within the range of 1870-1840 mln. years. The magmatism of the second stage (1747-1734 mln. years) is represented by the potassium granites and allochthonous charnockites, comparable by the composition with the A-type granites
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой